2009
DOI: 10.1016/j.jcrs.2009.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Glistenings in a large series of hydrophobic acrylic intraocular lenses

Abstract: The results suggest a potential association between the incidence of glistenings and IOL power and glaucoma, but not between glistenings and age, sex, IOL model, length of follow-up, CDVA, SE, or most ocular and systemic diseases and medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 20 publications
3
49
1
1
Order By: Relevance
“…1 Our research group evaluated and reported the incidence and severity of glistenings in a large study population with different types of Acrysof IOLs (Alcon Laboratories, Inc.) (260 eyes of 166 patients) and different lengths of follow-up (from 0 to 86 months). 8 We found that glistenings were present in 157 eyes (60.4%). The glistening severity was grade 1 in 87 eyes (33.5%) and grade 2 in 70 eyes (26.9%) according to a subjective classification used in the study.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…1 Our research group evaluated and reported the incidence and severity of glistenings in a large study population with different types of Acrysof IOLs (Alcon Laboratories, Inc.) (260 eyes of 166 patients) and different lengths of follow-up (from 0 to 86 months). 8 We found that glistenings were present in 157 eyes (60.4%). The glistening severity was grade 1 in 87 eyes (33.5%) and grade 2 in 70 eyes (26.9%) according to a subjective classification used in the study.…”
mentioning
confidence: 73%
“…3 Although most studies of glistenings report the incidence of the phenomenon in hydrophobic acrylic IOLs, [8][9][10][11][12][13][14][15][16] they have also been observed with other types of IOL materials, such as poly(methyl methacrylate) (PMMA), silicone, and hydrophilic acrylates. [17][18][19][20] Claims of an association between this phenomenon and decreased corrected distance visual acuity (CDVA) 1,8,11,16 and contrast sensitivity or with intraocular light scatter have been controversial. 13,14,21 The reported incidence of this phenomenon varies between studies as a function of several factors, such as length of postoperative follow-up, the type of IOL material, and the presence of postoperative inflammation.…”
mentioning
confidence: 99%
“…Several recent studies, based on large numbers of patients implanted with Acrysof IOLs (≈100 patients or more) conclude that moderate to severe/dense glistenings occur in 60-87% of patients implanted with these lenses [4,5,9,13,24]. The glistenings formation, as well as the severity of glistenings, has been correlated with longer follow-up times [3,7,10,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Four of these studies reported that glistenings had a significant negative effect on the high spatial frequency CS [1][2][3][4] and two studies were non-conclusive [5,6]. While some studies do show a decrease in VA with increased severity of glistenings [6,7] the general consensus in the literature tends to be that visual acuity is unaffected by glistenings [1][2][3]5,[8][9][10][11][12][13]. These studies found no common conclusion concerning the effect of glistenings on measured visual quality.…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increasing range of the problem, plenty of research is being conducted, describing and systematizing lesions in intraocular lenses after implantation [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, the majority of them concern IOL materials, while very few focus on the impact of lesions on visual quality.…”
mentioning
confidence: 99%